Ni-catalyzed dehydrogenative coupling of primary and secondary alcohols with methyl-N-heteroaromatics - Rana, Jagannath; Babu, Reshma; Subaramanian, Murugan; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2018)
Here we report the first base-metal catalyzed dehydrogenative coupling of primary (aromatic, heteroaromatic, and aliphatic) and secondary alcohols with methyl-N-heteroaromatics to form various C(sp(3))-alkylated N-heteroaromatics. The reaction is enabled by Earth abundant, non-precious NiBr2 as a transition metal catalyst and N,N,N,N-tetramethylethylenediamine (TMEDA) as a ligand system. Mechanistic studies reveal that a hydrogen auto-transfer process is involved in the direct C(sp(3))-alkylation and the reaction proceeds through an -olefination process.